Ecuador: Coyuntura social y política 2022-2023: Presentación del Dossier - Pacheco Lupercio, Fernanda (2023)
This issue brings together articles that analyze the Government of Guillermo Lasso, paying special attention to the policies implemented in the face of major national problems; Likewise, it analyzes the political conflict, mainizing the reading regarding the popular mobilizations of 2022; and finally, it offers an interpretation of the results of the 2023 sectional elections.